COVID-19 Forced Social Distancing and Isolation: A Multi-Perspective Experience - Janz, Bruce; Kaznina, Eka; Jihyun, Kim; Ammann, Claudia; Kohlberg, David; Mamali, Cătălin (ETHICS IN PROGRESS, 2020)
The article is combined of six chapters authored by these who voiced their experiences with social distancing during the COVID-19 pandemics in various contexts, but mostly centered on psychological, sociological, and ethical aspects. Authors, mostly psychologists and philosophers, were invited to describe their perspectives on the sense and practice of social distancing in times of pandemics. Their reflections seek to demonstrate various perspectives related to subjects’ novel self-experience, social situatedness, and their dealing with conventions and habits altered through the pandemics. As “the owl of Minerva takes its flight only when the shades of night are gathering” (Hegel), there is no conclusion in this article. It rather encourages other authors to reflect on the nearly global, still lasting phenomenon.